Groundbreaking for City Campus (Institutional Knowledge at Singapore Management University, 2002)
Members of Singapore Management University, Edward Cullinan Architects (Britain) and KNTA Architects (Singapore) at the groundbreaking ceremony for SMU’s campus at Bras Basah. KNTA Architects and Edward Cullinan Architects were awarded the design of the academic buildings and public open spaces. Photo taken on 27 March 2002.